1941
DOI: 10.1029/tr022i003p00603
|View full text |Cite
|
Sign up to set email alerts
|

Engineering calculations of suspended sediment

Abstract: The general theory of the vertical distribution of suspended sediment in a turbulent water stream has been sufficiently well established to permit its use in making calculations of the suspended material transportation in connection with engineering problems. It is the purpose of this paper to present simplified methods for making the necessary calculations of the total amount of sediment transported in suspension in a river or canal. Field‐data is presented for purposes of checking the validity of the various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(26 citation statements)
references
References 5 publications
0
24
0
2
Order By: Relevance
“…Though not described in this paper, Lane and Kalinske (1941), Einstein (1950), Brooks (1963), and Chang et al (1965) developed alternative methods to calculate q s . The two general approaches used to calculate the total noncohesive sediment load in an open channel consist of: (1) adding the separately estimated bedload and suspended load and (2) using a total load function that directly estimates the total amount of bedload and suspended load transport.…”
Section: Noncohesive Sediment Transportmentioning
confidence: 99%
“…Though not described in this paper, Lane and Kalinske (1941), Einstein (1950), Brooks (1963), and Chang et al (1965) developed alternative methods to calculate q s . The two general approaches used to calculate the total noncohesive sediment load in an open channel consist of: (1) adding the separately estimated bedload and suspended load and (2) using a total load function that directly estimates the total amount of bedload and suspended load transport.…”
Section: Noncohesive Sediment Transportmentioning
confidence: 99%
“…One of the most exciting advances made in the past few decades was by Ni and Wang (1991), who proved that a similar differential equation would be finally derived no matter which of the aforementioned theories was selected, which directly led to a generalized formula as an universal integral solution of the basic equation. Ni and his colleagues also demonstrated that most well-known formulas such as those proposed by Rouse (1937), Lane and Kalinske (1941), Hunt (1954), Ananian and Gerbashian (1965), Zagustin (1968), Laursen (1980), and Itakura and Kishi (1980) were merely special cases of the generalized formula under different conditions. This stimulated further studies which are still on-going (Cheng et al, 2013;Kundu and Ghoshal, 2014), the aim being to extend the general expression to an increasingly wide range of applicability.…”
Section: Sediment Fluxmentioning
confidence: 99%
“…As far as the suspended load is concerned, the distribution of the concentration of solids has been derived by linking such assumptions with further hypotheses on the nature of the stream turbulence and of sediment concentration at a reference height on the river bed (e.g. Rouse, 1937;Lane and Kalinske, 1941). However, one of the main criticisms of the hydraulically based approach is that the sediment transport is an intermittent process, strongly controlled by sediment availability.…”
Section: Introductionmentioning
confidence: 99%